1999
DOI: 10.1590/s0100-879x1999000500018
|View full text |Cite
|
Sign up to set email alerts
|

Collagen arrangement in hepatic granuloma in mice infected with Schistosoma mansoni: dependence on fiber radiation centers

Abstract: The collagen structure of isolated and in situ liver granuloma from Swiss Webster mice infected with Schistosoma mansoni was sequentially and three-dimensionally analyzed during different times of infection (early acute, acute, transitional acute-chronic, and chronic phases) by laser scanning confocal microscopy and electron scanning variable vacuum microscopy. The initial granuloma structure is characterized by vascular collagen residues and by anchorage points (or fiber radiation centers), from where collage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 14 publications
1
22
0
2
Order By: Relevance
“…It is possible that such findings are associated with differences in the organization of the lattice of collagen fibers built around schistosome eggs. In liver, the schistosomal granuloma is an organized structure, where the three-dimensional arrangement of its fibers, originating from anchorage points serves to provide increased tissue integrity and efficient distribution of soluble compounds and a haptotatic background to the cells (Lenzi et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that such findings are associated with differences in the organization of the lattice of collagen fibers built around schistosome eggs. In liver, the schistosomal granuloma is an organized structure, where the three-dimensional arrangement of its fibers, originating from anchorage points serves to provide increased tissue integrity and efficient distribution of soluble compounds and a haptotatic background to the cells (Lenzi et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Rakasz et al (1998) found that granulomas contained numerous activated Th1 and Th0 cells but that these were under tight control. have given a detailed morphogenic and biomechanical description of granuloma development and involution and have detailed the spatial deployment of collagen fibers within the granulomas (Lenzi et al 1999).…”
Section: The Formation Of Circumoval Granulomas and Modulation Of Gramentioning
confidence: 99%
“…Each growth unit acts as a fibrotic center as was previously described (Lenzi et al 1999). However, it is not formed by a single cell as was thought before, but it is originated in the interface between three or more cells, depending on the framework of the cellular arrangement, which determines the curvature or angles between collagen fibers (Figs 12,13).…”
Section: Discussionmentioning
confidence: 85%
“…In conclusion, the schistosome granuloma is an extremely complex system with transitory states where the fully organized structure ("little macrophagic metazoa") is literally greater than the sum of actions of its individual cells and extracellular matrix components (Lenzi et al 1999). The granuloma modulation is not only determined by immune external factors, but may also be influenced by internal constrictions and regulations that need to be better understood.…”
Section: Discussionmentioning
confidence: 99%